Disability Studies and the Language of Physical Education Curriculum - Susan S. Lee (Disability Studies Quarterly, 2011)
Disability studies questions taken-for-granted practices which can marginalize and exclude disabled students. Consciousness raising and questioning of attitudes and practices need to happen at all levels from educators to administrators to researchers to be able to transform a physical education curriculum. Meaningful change which desires the appearance of disability can facilitate future physical educators to learn and build positive attitudes towards working with disabled persons. Desiring disability is a critical paradigm shift from perceiving disabled persons as the “other” to embracing their individual and collective identities as valued lived experience. Disability studies provides a theoretical perspective to contribute to the discourses on special education, adapted physical education, personhood, and difference to reveal the complexity of the impact of taken-for-granted language in our everyday lives. Recommendations for changes to the language of university curriculum may contribute to the desire for the appearance of disability within higher education culture, and physical education practices.
Keywords: physical education; disability studies; curriculum; language; disability; adapted physical activity